Design of a Visual Query Language for Geographic Information System on a Touch Screen - Wu, Siju; Otmane, Samir; Moreau, Guillaume; Servières, Myriam (Human-Computer Interaction. Interaction Modalities and Techniques, 2013)
This paper presents two spatial query methods for a Geographic Information System (GIS) that runs on a touch screen. On conventional GIS interfaces SQL is used to construct spatial queries. However keyboard typing proves to be inefficient on touch screens. Furthermore, SQL is not an easy-learning language, especially for novices to GIS. To simplify query construction, firstly we have designed a map interaction based query method (MIBQM). This method allows users to make simple queries by selecting necessary layers, features and query operators directly on the interface. To allow users to construct complex queries, a sketch drawing based query method (SDBQM) is proposed. Spatial query concepts can be represented by sketches of some symbolic graphical objects. It is possible to add spatial conditions and non-spatial conditions to describe query concepts more precisely. An evaluation has been made to compare SQL and MIBQM. We have found that for simple queries, MIBQM takes less time and proves to be more user-friendly.